Lateral-torsional buckling behaviour of monosymmetric steel sections formed with flange upstands - Mudenda, Kenny (Department of Civil Engineering, 2024)
The study of the lateral-torsional buckling behaviour of steel beams has been largely focused on doubly symmetric beams and less so on monosymmetric sections. Monosymmetric sections, however, do offer some advantages over doubly symmetric beams if the monosymmetry is applied in a way that it can be exploited. This is because the effects of monosymmetry can work to increase or decrease the moment capacity. Identifying these cases is therefore essential. In the current study the behaviour of a monosymmetric section produced by introducing flange upstands as stiffeners is explored. The upstands convert a standard doubly symmetric section into a monosymmetric section. The change in member properties is first explored with the movement of shear center relative to the geometric centroid being of particular interest. It is observed that the shear center initially moves away from the centroid towards the stiffened flange, reaches a stationery point and then starts to move away from this flange. This leads to the shear center then intersecting the centroid so that for a monosymmetric section, at a certain upstand height, the shear center and centroid are coincident. This results in a monosymmetric section taking on a property typically associated with a doubly symmetric section. A study of the change in the monosymmetry constant of the section also reveals that at a given upstand height the monosymmetric section also takes on another property associated with doubly symmetric sections, that of the monosymmetry constant having a value of zero. Further study of the critical elastic moment change with change in upstand height reveals that the section initially has a significant increase in the value of the critical elastic moment with upstand height followed by a trend of diminishing increase rate. In some cases, this trend then reverses so that with an increase in upstand height the critical elastic moment starts to decrease. The region where the monosymmetry acts beneficially to increase section capacity represents a target domain before the monosymmetry then starts working to diminish the member capacity. This second region represents an undesirable domain for the use of these upstands. This observed behaviour, therefore, leads to identification of a domain of upstand heights in which the positive effect of monosymmetry can be exploited. The junction between the two regions, given by a critical upstand height, can be reasonably approximated based on the upstand height at which the shear center and centroid coincide. Engineers who may want to make use of flange stiffeners need to be aware of these trends to better manage the strengthening of doubly symmetric members so that material is used economically and not wasted in regions were the returns are minimal or diminishing. The application of this domain has been demonstrated for linear elastic buckling cases as well as for inelastic buckling cases so that real member behaviour is also simulated. Although applied for strengthening cases in the current study the principle can be used for section optimization at member selection stage should members with upstands be an option. Equations obtained using the Rayleigh-Ritz energy method were employed for the elastic critical buckling study for two transverse load cases. Finite element models were then employed for the nonlinear analysis for the inelastic buckling cases. Residual stresses have not been included in the finite element models. Geometric imperfections as well as material constitutive behaviour were incorporated in the models. This gives a realistic picture of ‘real' member behaviour despite not including residual stresses. The results from the nonlinear study support those from the linear elastic study in demonstrating how the beneficial domain can be exploited.